2016
DOI: 10.1002/adv.21686
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Polymer Ferroelectret: A Review on Their Development and Their Piezoelectric Properties

Abstract: Because of their ability to show ferroelectret behavior when exposed to an external electric field, cellular polymers have been recently considered for ferroelectret applications. These cellular polymer films can be produced by stretching or foaming, but depending on the application and conditions, different polymers, such as polypropylene (PP), poly(ethylene terephthalate), poly(ethylene naphthalate), poly(tetrafluoro ethylene), cross-linked PP, and some cyclo-olefines, have been considered. Nevertheless, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 114 publications
(505 reference statements)
3
89
1
Order By: Relevance
“…These holes of different shapes and sizes are sometimes filled with modifier particles. Such voids are usually responsible for the accumulation of piezoelectric charge in the polymeric materials [5][6][7][8][9]11]. In most cases, a lack of wettability and adhesion is observed, which is caused by immiscibility of components.…”
Section: Morphology Studies By Semmentioning
confidence: 99%
See 1 more Smart Citation
“…These holes of different shapes and sizes are sometimes filled with modifier particles. Such voids are usually responsible for the accumulation of piezoelectric charge in the polymeric materials [5][6][7][8][9]11]. In most cases, a lack of wettability and adhesion is observed, which is caused by immiscibility of components.…”
Section: Morphology Studies By Semmentioning
confidence: 99%
“…In such cavities, the electric charge is entrapped, which results in formation of permanent electric dipoles [5][6][7][8][9].…”
mentioning
confidence: 99%
“…flexibility, durability, low density) and the possibility of forming any shapes and sizes of products in conventional molding processes. It has been repeatedly confirmed that good piezoelectric properties have semicrystalline polymers with a cellular structure [14,[17][18][19][20]. On the basis of reviewing the current literature shows that an isotactic polypropylene is already recognized as a potential piezoelectric material (besides of PVDF or PFTE) [12][13][14][15][16], however, other polyolefins, including polyethylene, are still not well investigated.…”
mentioning
confidence: 99%
“…To ensure a maximum N 2 saturation, a stream of SC‐N 2 with a pressure of 7 MPa and a flow rate of 5 ml/min was injected in zone 2 of the extruder, which was controlled by a mass flow meter/controller model F‐201CV‐5 K0‐ABD‐22‐V (Hoskin Scientific Co., USA). More information on the experimental setup can be found in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…To achieve a good eye‐like cellular morphology, which is suitable for good piezoelectric properties, the samples were uniaxially stretched in the melt state between the die exit and the first roller of the calendar (distance of 10 cm). After some processing and composition optimization in terms of screw configuration, temperature profile, die temperature, stretching speed, and nucleating agent, different closed‐cell foamed PP films, with and without nucleating agent, were produced. The specifications of the selected samples studied here are reported in Table .…”
Section: Methodsmentioning
confidence: 99%